Strategi Aisyiyah dalam Mencetak Kader Pemimpin Perempuan Berbasis Spiritualitas (Studi Kasus Pimpinan Daerah Aisyiyah Kabupaten Jember) - Siti Nursyamsiyah; Sawitri Komarayanti (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
The socio-cultural life in today's society experiences a complete freedom since the existence of social networks, namely the expansion of the consumer's lifestyle. This condition requires a spiritual movement among women that can enlighten and spread the values of truth, goodness, moral aristocracy and social status. To meet these challenges, stratifications must be encouraged within the Aisyiyah's organization. To prepare women to be spiritual leaders who will be able to influence, serve and move the conscience of His servants in a very wise way through ethical and exemplary approaches, the Regional Leaders of Aisyiyah around Jember Regency optimizes ‘majlis tabligh’ in the muballighat corp meeting to increase the regeneration of their organizational objectives. This can also promote women to be spiritual leaders who can mobilize cadres in nearly all branches around Jember Regency to advocate amar ma'ruf nahi munkar as well as tajdid based on the teaching in the holy Qur'an and As-Sunnah. Women leaders as the hope of Muhammadiyah movements are women who are strong in ideology, maintain progressive thoughts and have a national perspective. Therefore, women leaders may be said to be based on spirituality if their leadership includes leadership for Aisyiyah, a leader for the ummah and a leader for the nation.